Politik Asik: Upaya Edukasi Politik menggunakan Media Board Game - Mustofa, Mustabsyirotul Ummah; Utama, Rafif Sakti; Paskarina, Caroline; Rahmatunnisa, Mudiyati; Herdiansah, Ari Ganjar (Jurnal SOLMA, 2024)
Background: The fast development of technology demands adjustments in political education. The "Politik Asik" community service programme is a political education effort that combines board games and learning media. This approach aims to improve political literacy and critical thinking skills, especially among young voters and women in welcoming the 2024 political year. Method: Politik Asik collaborates with various communities, PKK, high school students and village officials. With a political education model through board game media, fifty participants from each category, namely the youth and women categories. Result: Through analytical observations, the results show that this programme succeeded in increasing participants' political interest and participation, as well as developing better political literacy and critical thinking skills. The strength of the programme is its ability to attract participants' attention and create an interactive learning experience. Conclusion: This service activity confirms the importance of developing innovative political education methods to strengthen the participation of young voters and women, which in turn supports a stronger democracy in Indonesia.